Me & Rumi : the autobiography of Shams-l Tabrizi - Chittick, William C. (Gulshan Books Sri Nagar, 2015)
Me and Rumi: The Autobiography of Shams-i Tabrizi by William C. Chittick offers an in-depth exploration of the life, teachings, and spiritual philosophy of Shams-i Tabrizi, the enigmatic mentor of the renowned Persian poet and mystic, Jalal al-Din Rumi. Drawing from Maqalat-e Shams-e Tabrizi (The Discourses of Shams), Chittick provides a scholarly yet accessible translation and analysis of Shams' words, revealing his radical approach to spirituality, his critiques of religious orthodoxy, and his transformative impact on Rumi. The book delves into themes of divine love, self-annihilation, and the nature of true knowledge, illustrating how Shams' unconventional wisdom reshaped Rumi$1 (Bs poetic and mystical vision. By presenting Shams in his own words and contextualizing his ideas within Sufi tradition, Me and Rumi offers valuable insights into the spiritual dynamics that gave rise to some of the most profound poetry in Islamic mysticism.s